Las hermenéuticas del sí mismo : un acercamiento comprensivo a las dimensiones de la educación corporal (2011)
ABSTRACT: The following article aims to set up a comprehensive guidelines to give “body” to education and go Corporal epistemic elements defining its conceptual and methodological. These elements have as their starting point the understanding of narrative as a strategy of corporal education that allows close to the senses and meanings that subjects from the experience of body and life story. Thus, the narrative approach facilitates the hermeneutics of the self, from three fundamental considerations, which in turn route the writing is presented below: One of them raises “the imperative of experience” (Larrosa, 2003b, p.167) as what happens to us and binds us to the concept of expertise and experience life as meaningless. A second element is set from understanding one’s own body rather than the experience and the event, existential territory where the meaning of the event emerges. Finally, the hermeneutics of the self that are in the construction of the narrative plot, which assumes the life story and “body as they are the people” (Ricoeur, 2003, p.9) are the foundation of the process of identity formation and self-creation of subjectivity that let you customize the dimensions of corporal education, aesthetics, poetics, and ontological.